A national health impact assessment of achieving tree canopy goals in US urban areas - Michelle C. Kondo; Tamara Iungman; Evelise Pereira Barboza; Dexter H. Locke; Ray Yeager; Dustin Fry; Ava-Clare Steed; Marcia Pescador Jiménez; David Rojas-Rueda; Mark Nieuwenhuijsen (Environmental Research, 2026)

Relations of residential greenness with immunity and inflammation - Daniel W. Riggs; Sonia Cobbold; Clara G. Sears; Marina V. Malovichko; Israel Sithu; Brian E. Sansbury; Ray Yeager; Marcin Wysoczynski; Sanjay Srivastava; Rachel J. Keith; Aruni Bhatnagar (Environmental Research, 2026)

Expert perspectives on exposure-response functions for urban health policy: Lessons from a UBDPolicy workshop - Harry Williams; Zorana Jovanovic Andersen; Hanna Boogaard; Søren Brage; Matthew H.E.M. Browning; Samuel Cai; Xuan Chen; Priyanka deSouza; Angel M. Dzhambov; Benjamin Fenech; Gillian Flower; Francesco Forastiere; et al. (Environmental Research, 2026)

Intra-neighborhood associations between residential greenness and blood pressure - Ray Yeager; Rachel J. Keith; Daniel W. Riggs; Daniel Fleischer; Matthew H.E.M. Browning; Alessandro Ossola; Kandi L. Walker; Joy L. Hart; Sanjay Srivastava; Shesh N. Rai; Ted Smith; Aruni Bhatnagar (Science of The Total Environment, 2024)

Reconstructing 120 years of climate change impacts on Joshua tree flowering - Jeremy B. Yoder; Ana Karina Andrade; Lesley A. DeFalco; Todd C. Esque; Colin J. Carlson; Daniel F. Shryock; Ray Yeager; Christopher I. Smith (Ecology Letters, 2024)
Quantifying how global change impacts wild populations remains challenging, especially for species poorly represented by systematic datasets. Here, we infer climate change effects on masting by Joshua trees ( Yucca brevifolia and Y. jaegeriana ), keystone perennials of the Mojave Desert, from 15 years of crowdsourced observations. We annotated phenophase in 10,212 geo‐referenced images of Joshua trees on the iNaturalist crowdsourcing platform, and used them to train machine learning models predicting flowering from annual weather records. Hindcasting to 1900 with a trained model successfully recovers flowering events in independent historical records and reveals a slightly rising frequency of conditions supporting flowering since the early 20th Century. This reflects increased variation in annual precipitation, which drives masting events in wet years—but also increasing temperatures and drought stress, which may have net negative impacts on recruitment. Our findings reaffirm the value of crowdsourcing for understanding climate change impacts on biodiversity.

The paradox of high greenness and poor health in rural Central Appalachia - Jiaying Dong; Matthew H.E.M. Browning; Aaron Reuben; Olivia McAnirlin; Shuai Yuan; Claude Stephens; Mildred Maisonet; Kuiran Zhang; Jaime E. Hart; Peter James; Ray Yeager (Environmental Research, 2024)

Combining Community Wastewater Genomic Surveillance with State Clinical Surveillance: A Framework for SARS-CoV-2 Public Health Practice - Ted Smith; Rochelle H. Holm; Ray Yeager; Joseph B. Moore; Eric C. Rouchka; Kevin J. Sokoloski; Erin M. Elliott; Daymond Talley; Vaneet Arora; Sarah Moyer; Aruni Bhatnagar (Food and Environmental Virology, 2022)
This study aimed to develop a framework for combining community wastewater surveillance with state clinical surveillance for the confirmation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants within the community and to provide recommendations on how to expand on such research and apply the findings in public health responses. Wastewater samples were collected weekly from 17 geographically resolved locations in Louisville/Jefferson County, Kentucky (USA), from February 10 to December 13, 2021. Genomic surveillance and quantitative reverse transcription PCR (RT-qPCR) platforms were used to screen for SARS-CoV-2 in wastewater, and state clinical surveillance was used for confirmation. The study results highlighted an increased epidemiological value of combining community wastewater genomic surveillance and RT-qPCR with conventional case-auditing methods. The spatial scale and temporal frequency of wastewater sampling provided promising sensitivity and specificity for gaining public health screening insights about SARS-CoV-2 emergence, seeding, and spread in communities. Improved national surveillance systems are needed against future pathogens and variants, and wastewater-based genomic surveillance exhibits great potential when coupled with clinical testing. This paper presents evidence that complementary wastewater and clinical testing are cost-effectively enhanced when used in combination, as they provide a strong tool for a joint public health framework. Future pathogens of interest may be examined in either a targeted fashion or using a more global approach where all pathogens are monitored. This study has also provided novel insights developed from evidence-based public health practices.